Efeito da restrição hídrica sobre o crescimento de clones de eucalipto - Xavier, Talita Miranda Teixeira (2014)
The establishment and early field grown of forest tree species are strongly affected by the availability of soil water and planting season. The aim of this work was to study the impact of soil water stress on growth of young plants of two hybrid clones of